Measurement of the charge asymmetry in top-quark pair production in association with a photon with the ATLAS experiment - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; et al. (Physics letters, 2023)
A measurement of the charge asymmetry in top-quark pair (tt¯) production in association with a photon is presented. The measurement is performed in the single-lepton tt¯ decay channel using proton-proton collision data collected with the ATLAS detector at the Large Hadron Collider at CERN at a centre-of-mass-energy of 13 TeV during the years 2015-2018, corresponding to an integrated luminosity of 139 fb−1. The charge asymmetry is obtained from the distribution of the difference of the absolute rapidities of the top quark and antiquark using a profile likelihood unfolding approach. It is measured to be AC=−0.003±0.029 in agreement with the Standard Model expectation.
Gesehen am 07.07.2025
Online verfügbar: 20. Juni 2023
*The ATLAS Collaboration: G. Aad, L.M. Baltes, F. Bartels, F.L. Castillo, M.M. Czurylo, M. Dunford, S. Franchino, M. Klassen, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, S. Rodriguez Bosca, C. Sauer, A. Schoening, H-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, J. Zinsser [und 2912 weitere Personen]